NATURAL SPECIATION OF ZN AT THE MICROMETER SCALE IN A CLAYEY SOIL USING X-RAY FLUORESCENCE, ABSORPTION, AND DIFFRACTION - Manceau A.; Proux O.; Geoffroy N.; Lanson B.; Marcus M.A.; Tamura N. (My University, 2004)
Combined use of synchrotron-based X-ray fluorescence (SXRF), diffraction (XRD), and absorption (EXAFS) with an X-ray spot size as small as five micrometers allows us to examine noninvasively heterogeneous soils and sediments. Specifically, the speciation of trace metals at low bulk concentrations and the nature of host minerals can be probed with a level of detail unattainable by other techniques. The potential of this novel analytical approach is demonstrated by determining the Zn species in the solid phases of a pristine horizon of a clayey acidic soil (pH 4.5–5.0) having a Zn concentration of 128 mg/kg. The sample presents a differentiated fabric under the optical microscope with traces of localized manganiferous, ferriferous and argillaceous accumulations. The high chemical and textural heterogeneity of this soil offers an opportunity to identify new Zn species and to confirm the existence of others proposed from published least-squares fits of bulk averaged EXAFS spectra. As many as five to six Zn species were observed: sphalerite (ZnS), zincochromite (ZnCr2O4), Zn-containing phyllosilicate and lithiophorite, and Zn-sorbed ferrihydrite or Zn-phosphate, the results being less definitive for these two last species. Bulk EXAFS spectroscopy applied to the powdered soil indicated that Zn is predominantly associated with phyllosilicates, all other species amounting to < ~10 to 20% of total zinc. The role of lithiophorite in the sequestration of zinc in soils had been inferred previously, but the firm identification of lithiophorite in this study serves as an excellent demonstration of the capabilities of combined micro-SXRF/XRD/EXAFS measurements. The micro-EXAFS spectrum collected in an area containing only phyllosilicates could not be simulated assuming a single Zn structural environment. Two distinct octahedrally-coordinated crystallographic sites (i.e., two EXAFS components) were considered: one site located within the phyllosilicate structure (isomorphic cationic substitution in the octahedral sheet) and another in the interlayer region in the form of a Zn-sorbed hydroxy-Al interlayered species. This second subspecies is less certain and further investigation of the individual EXAFS spectrum of this component is needed to precise its exact nature and the uptake mechanism of zinc in it.